Effect of BiFeO3/epoxy resin composite thickness on gigahertz microwave absorption properties - Rusly, Siti Nor Ain; Matori, Khamirul Amin; Ismail, Ismayadi; Abbas, Zulkifly; Ibrahim, Idza Riati (2018)
The microwave absorption properties of multiferroic BiFeO3 (BFO) epoxy resin composite with different thicknesses have been investigated. The BiFeO3 nanoparticles were synthesized by using high energy ball milling (HEBM). The BiFeO3 powders 70% by weight were mixed with epoxy resin as a matrix to form a composite with verified thicknesses of 1 mm, 2 mm and 3 mm. XRD was used to identify the phases and structures of the sample. The room temperature of magnetic characteristics of BFO composite was analyzed by using a vibrating sample magnetometer. The reflection loss value for the purpose of absorption performance was measured in the frequency range 8-18 GHz using a network analyzer. The absorption performances of different thickness of BFO epoxy resin composites were compared and analyzed. The results revealed that BFO epoxy resin composites with 3 mm thickness exhibited higher absorption performance with RLmin of –40.5 dB over a 1.31 GHz bandwidth (corresponding to RL below -10 dB).